2003
DOI: 10.1088/0953-8984/16/2/025
|View full text |Cite
|
Sign up to set email alerts
|

The characterization of high quality multicrystalline silicon by the electron beam induced current method

Abstract: Multicrystalline silicon (mc-Si) manufactured by a multi-stage solidification control casting method has been characterized by the electron beam induced current (EBIC) method. The average diffusion length of the ingot was over 250 µm, which was much longer than that of conventional mc-Si. The EBIC study revealed that the electrical activities of grain boundaries (GBs) varied with the ingot position due to the impurity contamination level. The main impurity detected was iron. The concentration of iron in the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 17 publications
(22 reference statements)
0
16
0
Order By: Relevance
“…Therefore, both crystalline defects and contaminated Fe impurities in cast-mc-Si are factors causing deterioration in the conversion efficiency of solar cells. The electrical properties at crystal defects in cast-mc-Si were evaluated by measuring the minority carrier lifetimes [9] and electron beam-induced current (EBIC) [6][7][8]10]. It has been reported that the minority carrier lifetime measured by the microwave detection of photo-conductive decay (m-PCD) method is especially low in regions where the density of sub-grain-boundaries is high [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, both crystalline defects and contaminated Fe impurities in cast-mc-Si are factors causing deterioration in the conversion efficiency of solar cells. The electrical properties at crystal defects in cast-mc-Si were evaluated by measuring the minority carrier lifetimes [9] and electron beam-induced current (EBIC) [6][7][8]10]. It has been reported that the minority carrier lifetime measured by the microwave detection of photo-conductive decay (m-PCD) method is especially low in regions where the density of sub-grain-boundaries is high [9].…”
Section: Introductionmentioning
confidence: 99%
“…EBIC contrast at sub-grain-boundaries was stronger than at random grain boundaries and coincidence site lattice boundaries such as S3, S9 and S27 [6,7], indicating that the sub-grain boundary acts as stronger recombination center. However, it is well known that Fe impurities in the cast-mc-Si concentrate around crystalline defects such as grain boundaries [6][7][8]10], and it is therefore very important to differentiate between the influence of crystalline defects and Fe contamination on carrier recombination in cast-mc-Si.…”
Section: Introductionmentioning
confidence: 99%
“…It is not necessary to stress that the key to improve the efficiency of mc-Si solar cell is the control of grain boundaries (GBs) and impurity contaminations. It is widely accepted that the GBs and sub-boundaries give serious suppression of solar cell efficiency [1][2][3][4].The impurity contamination, mainly Fe, also degrades the efficiency very much [5][6][7][8][9]. In commercial mc-Si wafers, these two defects closely interact with each other and determine the solar cell efficiency.…”
mentioning
confidence: 99%
“…It gives us the information that except that the defects and grain boundary should influence cells LID, the impurity content of wafers also could make big contribution on cells LID. As the literatures introduction, the minority carrier lifetime is directly associated with impurity, defects, crystal boundary and so on (4). It is instructive examine if the LID in the cells is fully controlled by the degradation in minority carrier lifetime.…”
Section: Methodsmentioning
confidence: 99%